Increased Oxidative Stress Markers in Cerebrospinal Fluid from Healthy Subjects with Parkinson’s Disease-Associated LRRK2 Gene Mutations - Loeffler, David A.; Klaver, Andrea C.; Coffey, Mary P.; Aasly, Jan O.; LeWitt, Peter A. (Frontiers in Aging Neuroscience, 2017)
Mutations in the leucine-rich repeat kinase 2 (LRRK2) gene are the most frequent cause of inherited Parkinson's disease (PD). The most common PD-associated LRRK2 mutation, G2019S, induces increased production of reactive oxygen species in vitro. We therefore hypothesized that individuals with PD-associated LRRK2 mutations might have increased concentrations of oxidative stress markers and/or decreased total antioxidant capacity (TAC) in their cerebrospinal fluid (CSF). We measured two oxidative stress markers, 8-hydroxy-2’-deoxyguanosine (8-OHdG) and 8-isoprostane (8-ISO), and TAC in CSF from LRRK2 mutation-bearing PD patients (LRRK2 PD = 19), sporadic PD patients (sPD = 31), and healthy control subjects with or without these mutations (LRRK2 CTL = 30, CTL = 27). 8-OHdG and 8-ISO levels were increased in LRRK2 CTL subjects, while TAC was similar between groups. 8-ISO was negatively correlated, and TAC was positively correlated, with Montreal Cognitive Assessment (MoCA) scores in LRRK2 PD, LRRK2 CTL, and CTL subjects. Correlations in both groups of PD patients between the two oxidative stress markers and Unified Parkinson Disease Rating Scale (UPDRS) Total scores were weak, while TAC was negatively correlated with these scores. These findings suggest that oxidative stress may be increased in the CNS in healthy individuals with PD-associated LRRK2 mutations, perhaps contributing to their risk for PD. Further, TAC may decrease in the CNS with the progression of PD, and when cognitive impairment is present regardless of the presence or absence of PD.